Anti-static surface protective film

JP2024178183AActive Publication Date: 2024-12-24ZACROS CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024145390
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-24
Estimated Expiration
2036-02-29

AI Technical Summary

Benefits of technology

【0028】 本発明の帯電防止表面保護フィルムは、被着体に対する汚染が少なく、被着体に対する低汚染性が経時変化しない。また、本発明によれば、LR偏光板やAG-LR偏光板などの、被着体の表面が、シリコーン化合物やフッ素化合物などで防汚染処理してある光学用フィルムであっても、帯電防止表面保護フィルムを、被着体から剥離する時に発生する剥離帯電圧を低く抑えることができ、経時劣化しないで優れた剥離帯電防止性能を有する帯電防止表面保護フィルムを提供できる。 本発明の帯電防止表面保護フィルムによれば、光学用フィルムの表面を確実に保護することができることから、生産性の向上と歩留まりの向上を図ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178183000001_ABST
    Figure 2024178183000001_ABST
Patent Text Reader

Abstract

To provide an antistatic surface protective film which causes little stain of an adherend, does not deteriorate with time, and has excellent peeling anti-static performance.SOLUTION: An antistatic surface protective film includes: an adhesive layer 2 that is formed by cross-linking an acrylic polymer of a copolymer, which is formed by copolymerizing (a1) 10 to 30 parts by weight of a (meth)acrylate ester monomer having the number of carbon atoms of C1 to C4 in its alkyl group, (a2) 70 to 90 parts by weight of a (meth)acrylate ester monomer having the number of carbon atoms of C5 to C18 in its alkyl group, B) 0.1 to 12 parts by weight of a copolymerizable monomer containing a hydroxyl group, and (F) 5 to 50 parts by weight of a polyalkylene glycol mono(meth)acrylic acid ester monomer, with an adhesive composition containing a crosslinking agent; and a release film 5 that is a release agent layer 4 containing an anti-static agent, which is laminated on one surface of a resin film 3, and that is laminated on a surface of the adhesive layer 2 through the release agent layer 4.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antistatic surface protective film. More specifically, the present invention relates to a method for producing an antistatic surface protective film having antistatic properties, and an antistatic surface protective film, and provides a method for producing an antistatic surface protective film that causes little contamination of an adherend, does not deteriorate over time, and has excellent peel-off antistatic properties, and an antistatic surface protective film. [Background technology]

[0002] When optical films such as polarizing plates, retardation plates, lens films for displays, anti-reflection films, hard coat films, transparent conductive films for touch panels, and other optical products such as displays using the same are manufactured and transported, a surface protective film is attached to the surface of the optical film to prevent the surface from being soiled or scratched in later processes. In order to improve work efficiency by eliminating the need to peel off the surface protective film and then reattach it, the appearance inspection of the optical film, which is a product, is sometimes performed with the surface protective film attached to the optical film. Conventionally, a surface protection film having a pressure-sensitive adhesive layer on one side of a base film has been generally used in the manufacturing process of optical products to prevent scratches and dirt from adhering. The surface protection film is attached to an optical film via a pressure-sensitive adhesive layer having a weak adhesive strength. The pressure-sensitive adhesive layer has a weak adhesive strength so that the used surface protection film can be easily peeled off when peeled off and removed from the surface of the optical film, and the pressure-sensitive adhesive does not adhere to and remain on the optical film of the product, which is the adherend (so-called, to prevent the occurrence of adhesive residue).

[0003] In recent years, during the production process of liquid crystal display panels, there have been rare cases where the peeling charge voltage that is generated when peeling off and removing the surface protection film that has been laminated on top of the optical film has destroyed circuit components such as driver ICs that control the display screen of the liquid crystal display panel, or damaged the alignment of liquid crystal molecules. In addition, in order to reduce the power consumption of liquid crystal display panels, the driving voltage of liquid crystal materials has been lowered, and as a result, the breakdown voltage of driver ICs has also been lowered. Recently, there has been a demand for the peeling electrification voltage to be within the range of +0.7kV to -0.7kV. For this reason, in order to prevent problems caused by high peeling electrification voltage when peeling the surface protection film from the adherend, an adhesive layer containing an antistatic agent for keeping the peeling electrification voltage low has been proposed.

[0004] For example, Patent Document 1 discloses a surface protection film that uses a pressure-sensitive adhesive made of an alkyltrimethylammonium salt, a hydroxyl group-containing acrylic polymer, and a polyisocyanate. Furthermore, Patent Document 2 discloses a pressure-sensitive adhesive composition comprising an ionic liquid and an acrylic polymer having an acid value of 1.0 or less, and pressure-sensitive adhesive sheets using the same. Furthermore, Patent Document 3 discloses an adhesive composition comprising an acrylic polymer, a polyether polyol compound, and an alkali metal salt treated with an anion-adsorbing compound, and a surface protection film using the same. Furthermore, Patent Document 4 discloses a pressure-sensitive adhesive composition comprising an ionic liquid, an alkali metal salt, and a polymer having a glass transition temperature of 0° C. or lower, and a surface protection film using the same. Furthermore, Patent Documents 5 and 6 disclose mixing polyether-modified silicone into the pressure-sensitive adhesive layer of a surface protection film. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-131957 A [Patent Document 2] JP 2005-330464 A [Patent Document 3] JP 2005-314476 A [Patent Document 4] JP 2006-152235 A [Patent Document 5] JP 2009-275128 A [Patent Document 6] Patent No. 4537450 Summary of the Invention [Problem to be solved by the invention]

[0006] In the above Patent Documents 1 to 4, an antistatic agent is added inside the adhesive layer, but the thicker the adhesive layer is, and the more time passes, the more the amount of antistatic agent that migrates from the adhesive layer to the adherend to which the surface protection film is attached increases. In addition, in optical films such as LR (Low Reflective) polarizing plates and AG (Anti Glare)-LR polarizing plates, the surface of the optical film is treated for anti-contamination with silicone compounds, fluorine compounds, etc., so that the peeling electrification voltage increases when the surface protection film used for such optical films is peeled off from the optical film that is the adherend.

[0007] In addition, when polyether-modified silicone is mixed into the adhesive layer as described in Patent Documents 5 and 6, it is difficult to finely adjust the adhesive strength of the surface protection film. In addition, since polyether-modified silicone is mixed into the adhesive layer, if the conditions for applying and drying the adhesive composition onto the base film change, the surface characteristics of the adhesive layer on which the surface protection film is formed change subtly. Furthermore, from the viewpoint of protecting the surface of the optical film, the thickness of the adhesive layer cannot be made extremely thin. Therefore, it is necessary to increase the amount of polyether-modified silicone mixed into the adhesive layer depending on the thickness of the adhesive layer, and as a result, the surface of the adherend becomes easily contaminated, and the adhesive strength and the contaminating property to the adherend change over time.

[0008] In recent years, with the spread of 3D displays (stereoscopic displays), there are some in which an FPR (Film Patterned Retarder) film is laminated to the surface of an optical film such as a polarizing plate. The FPR film is laminated after peeling off the surface protective film that was laminated to the surface of the optical film such as a polarizing plate. However, if the surface of the optical film such as a polarizing plate is contaminated by the adhesive or antistatic agent used in the surface protective film, there is a problem that the FPR film is difficult to adhere to. For this reason, surface protective films used for such applications are required to be ones that cause little contamination to the adherend.

[0009] On the other hand, some liquid crystal panel manufacturers have adopted a method for evaluating the fouling property of a surface protective film on an adherend, in which the surface protective film attached to an optical film such as a polarizing plate is once peeled off, reattached in a state in which air bubbles are mixed in, heat-treated under a specified condition, and then the surface protective film is peeled off to observe the surface of the adherend. In this evaluation method, even if the surface contamination of the adherend is small, if there is a difference in the surface contamination of the adherend between the part where the air bubbles are mixed in and the part where the adhesive of the surface protective film was in contact, the trace of the air bubbles (sometimes called air bubble stains) remains. Therefore, this is a very strict evaluation method for evaluating the fouling property on the surface of the adherend. In recent years, there has been a demand for a surface protective film that does not have a problem with fouling property on the surface of the adherend even in the results of such a strict evaluation method. However, it has been difficult to solve this problem with a surface protective film using an adhesive layer containing an antistatic agent, which has been proposed in the past.

[0010] For this reason, there is a need for a surface protection film for use with an optical film that causes very little contamination of an adherend and that does not change with time with respect to the contamination of the adherend.Furthermore, there is a need for a surface protection film that suppresses the peeling electrification voltage when peeled off from an adherend.

[0011] The present inventors have conducted extensive research into solving this problem. In order to reduce contamination of the adherend and to reduce the change over time in antistatic performance, it is necessary to reduce the amount of antistatic agent added, which is presumed to be the cause of contamination of the adherend. However, when the amount of antistatic agent added is reduced, the peeling electrification voltage increases when the surface protective film is peeled off from the adherend. The present inventors have studied a method for suppressing the peeling electrification voltage when the surface protective film is peeled off from the adherend without increasing the absolute amount of the antistatic agent added. As a result, they have found that the peeling electrification voltage can be suppressed low when the surface protective film is peeled off from the adherend, which is the optical film, by applying an appropriate amount of an antistatic agent component to the surface of the adhesive layer after laminating the adhesive layer by coating and drying the adhesive composition, rather than adding and mixing an antistatic agent into the adhesive composition to form an adhesive layer, and have completed the present invention.

[0012] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for producing an antistatic surface protective film that causes little contamination of an adherend, does not deteriorate over time, and has excellent peel-off antistatic performance, and an antistatic surface protective film. [Means for solving the problem]

[0013] In order to solve the above problems, the technical concept of the antistatic surface protection film of the present invention is to apply an appropriate amount of antistatic agent to the surface of the adhesive layer after coating and drying an adhesive composition to laminate the adhesive layer, thereby minimizing the contamination of the adherend and minimizing the peel electrification voltage when peeled off from the adherend, that is, the optical film.

[0014] In order to solve the above-mentioned problems, the present invention provides an antistatic surface protection film comprising a substrate made of a transparent resin and a pressure-sensitive adhesive layer formed by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent, the substrate being formed on one side of the substrate, and a release film comprising a resin film and a release agent layer containing an antistatic agent laminated on one side of the substrate being laminated on the surface of the pressure-sensitive adhesive layer via the release agent layer, the acrylic polymer comprising an acrylic polymer of a copolymer obtained by copolymerizing a total of 100 parts by weight of (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18 and (B) 0.1 to 12 parts by weight of at least one copolymerizable monomer having a hydroxyl group, the total of 100 parts by weight of the (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18 being 1 to 30 parts by weight of (a1) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4 and (a2) 0.1 to 12 parts by weight of (a3) ​​0.1 to 12 parts by weight of (a4) 0.1 to 12 parts by weight of (a5) 0.1 to 12 parts by weight of (a6) 0.1 to 12 parts by weight of (a7) 0.1 to 12 parts by weight of (a8) 0.1 to 12 parts by weight of (a9) 0.1 to 12 parts by weight of (a10) the acrylic polymer is not copolymerized with a copolymerizable monomer containing a carboxyl group and a nitrogen-containing vinyl monomer not containing a hydroxyl group, and (a1) the at least one (meth)acrylic ester monomer having an alkyl group with a carbon number of C1 to C4 is at least one selected from the group consisting of methyl (meth)acrylate and ethyl (meth)acrylate, the pressure-sensitive adhesive composition further contains (C) a difunctional or higher isocyanate compound, (D) a crosslinking accelerator, and (E) a keto-enol tautomer compound, and does not contain an antistatic agent, and the release agent layer is formed from a resin composition containing a release agent mainly composed of dimethylpolysiloxane and an antistatic agent. The present invention also provides an antistatic surface protective film in a state where the release film has been peeled off, in which the antistatic agent in the release agent layer is transferred to the surface of the adhesive layer when the release film is peeled off from the surface of the adhesive layer of the antistatic surface protective film, and the antistatic surface protective film is characterized in that when the antistatic surface protective film is attached to a polarizing plate that has been subjected to a low-reflection surface treatment as an adherend via the adhesive layer, and then the adhesive layer is peeled off from the polarizing plate, no contamination is found on the surface of the polarizing plate.

[0015] The pressure-sensitive adhesive composition preferably contains (F) a polyalkylene glycol mono(meth)acrylate monomer in which the average repeat number of alkylene oxides constituting the polyalkylene glycol chain is 3 to 14 and the diester content in the monomer is 0.2% or less.

[0016] The antistatic agent in the release agent layer is preferably an alkali metal salt.

[0017] Further, in order to solve the above-mentioned problems, the present invention provides an antistatic surface protection film comprising a substrate film made of a transparent resin and a pressure-sensitive adhesive layer formed on one side thereof by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer, wherein the acrylic polymer is an acrylic polymer of a copolymer obtained by copolymerizing, relative to a total of 100 parts by weight of (A) (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18, 1 to 30 parts by weight of (a1) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C4, 70 to 99 parts by weight of (a2) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18, and 0.1 to 12 parts by weight of (B) at least one copolymerizable monomer containing a hydroxyl group, as a copolymerizable monomer group, the pressure-sensitive adhesive composition further comprises (C) a bifunctional or higher isocyanate compound, (D) a crosslinking accelerator, and (E) a keto-enol tautomer compound; a release film having a release agent layer containing an antistatic agent laminated on one side of a resin film is bonded to the surface of the pressure-sensitive adhesive layer via the release agent layer, the antistatic agent from the release agent layer being transferred to the surface of the pressure-sensitive adhesive layer, the release agent layer being formed from a resin composition containing a release agent mainly composed of dimethylpolysiloxane, a silicone-based compound that is liquid at 20°C, and an antistatic agent; and the pressure-sensitive adhesive layer is bonded to a polarizing plate that has been subjected to a low-reflection surface treatment, and then peeled off, exhibiting good contamination resistance.

[0018] In addition, it is preferable that the pressure-sensitive adhesive composition further contains 0 to 50 parts by weight (however, it may be absent) of (F) a polyalkylene glycol mono(meth)acrylic acid ester monomer in which the average repeating number of alkylene oxides constituting the polyalkylene glycol chain is 3 to 14 and the diester content in the monomer is 0.2% or less, relative to a total of 100 parts by weight of (A) (meth)acrylic acid ester monomers in which the alkyl group has carbon atoms of C1 to C18.

[0019] It is also preferred that the (D) crosslinking accelerator is at least one selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds, is contained in an amount of 0.001 to 0.5 parts by weight relative to 100 parts by weight of the acrylic polymer, contains the (E) keto-enol tautomer compound in an amount of 0.1 to 300 parts by weight, and the weight ratio of (E) / (D) is 70 to 1000.

[0020] The (B) hydroxyl group-containing copolymerizable monomer is preferably at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide, and is preferably present in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the acrylic polymer.

[0021] The (C) difunctional or higher isocyanate compound may be, for example, an acyclic aliphatic isocyanate compound produced by reacting a diisocyanate compound with a diol compound, and the diisocyanate compound may be an aliphatic diisocyanate selected from the group of compounds consisting of tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate; and for the diol compound, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol monohydroxypivalate, polyethylene glycol, polyisocyanate, tert-butyl-1,3-propanediol ... The trifunctional isocyanate compound is an isocyanurate of a hexamethylene diisocyanate compound, an isocyanurate of an isophorone diisocyanate compound, an adduct of a hexamethylene diisocyanate compound, an adduct of an isophorone diisocyanate compound, a biuret of a hexamethylene diisocyanate compound, a biuret of an isophorone diisocyanate compound, an isocyanurate of a tolylene diisocyanate compound, an isocyanurate of a xylylene diisocyanate compound, an isocyanurate of a hydrogenated xylylene diisocyanate compound, an adduct of a tolylene diisocyanate compound, an adduct of a xylylene diisocyanate compound, and an adduct of a hydrogenated xylylene diisocyanate compound, and is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of the acrylic polymer.

[0022] The pressure-sensitive adhesive composition preferably contains (H) a polyether-modified siloxane compound having an HLB value of 7 to 15 in an amount of 1.0 part by weight or less (except for the case of 0 part by weight) per 100 parts by weight of the acrylic polymer.

[0023] The silicone compound in the release agent layer is preferably a polyether-modified silicone.

[0024] The antistatic agent in the release agent layer is preferably an alkali metal salt.

[0025] The antistatic agent in the release agent layer is preferably a Li salt, and is at least one selected from the group consisting of LiTFSI, LiFSI, and LiTF.

[0026] The present invention also provides an optical film comprising the above-mentioned antistatic surface protection film laminated thereto.

[0027] The present invention also provides an optical component having the above-mentioned antistatic surface protection film laminated thereto. Effect of the Invention

[0028] The antistatic surface protective film of the present invention causes little contamination of the adherend, and the low contamination property of the adherend does not change over time. Furthermore, according to the present invention, even if the adherend is an optical film whose surface has been anti-contamination treated with a silicone compound, a fluorine compound, or the like, such as an LR polarizing plate or an AG-LR polarizing plate, the peeling electrification voltage generated when the antistatic surface protective film is peeled off from the adherend can be kept low, and an antistatic surface protective film having excellent peeling antistatic performance without deterioration over time can be provided. According to the antistatic surface protective film of the present invention, the surface of an optical film can be reliably protected, and therefore the productivity and yield can be improved. [Brief description of the drawings]

[0029] [Figure 1] 1 is a cross-sectional view illustrating the concept of an antistatic surface protective film of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a state in which the release film has been peeled off from the antistatic surface protective film of the present invention. [Diagram 3]FIG. 1 is a cross-sectional view showing one embodiment of an optical component according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, the present invention will be described in detail based on the embodiments. Fig. 1 is a cross-sectional view showing the concept of the antistatic surface protective film of the present invention. This antistatic surface protective film 10 has an adhesive layer 2 formed on one surface of a transparent base film 1. A release film 5 having a release agent layer 4 formed on the surface of a resin film 3 is attached to the surface of this adhesive layer 2.

[0031] The base film 1 used in the antistatic surface protective film 10 according to the present invention is made of a transparent and flexible resin. This allows the appearance inspection of the optical component to be performed while the antistatic surface protective film is attached to the optical component to be adhered. The film made of a transparent resin used as the base film 1 is preferably a polyester film such as polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, or polybutylene terephthalate. In addition to polyester films, films made of other resins can also be used as long as they have the necessary strength and optical suitability. The base film 1 may be a non-stretched film or a uniaxially or biaxially stretched film. In addition, the stretching ratio of the stretched film and the axial orientation angle formed by the crystallization of the stretched film may be controlled to a specific value. The thickness of the substrate film 1 used in the antistatic surface protection film 10 according to the present invention is not particularly limited, but is preferably about 12 to 100 μm, and more preferably about 20 to 50 μm for ease of handling. If necessary, an antifouling layer for preventing surface staining, an antistatic layer, a hard coat layer for preventing scratches, etc. may be provided on the surface of the base film 1 opposite to the surface on which the pressure-sensitive adhesive layer 2 is formed. The surface of the base film 1 may also be subjected to an easy-adhesion treatment such as surface modification by corona discharge or application of an anchor coating agent.

[0032] Furthermore, the adhesive layer 2 used in the antistatic surface protection film 10 of the present invention is not particularly limited as long as it adheres to the surface of the adherend, can be easily peeled off after use, and is unlikely to contaminate the adherend. However, taking into consideration durability after application to an optical film, it is common to use an acrylic adhesive obtained by crosslinking an adhesive composition containing an acrylic polymer.

[0033] In particular, a pressure-sensitive adhesive layer is preferred in which the acrylic polymer is an acrylic polymer copolymer obtained by copolymerizing, as (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18, (a1) at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4 and (a2) at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C5 to C18, and, as a copolymerizable monomer group, (B) at least one kind of copolymerizable monomer containing a hydroxyl group. The group of copolymerizable monomers may further include (F) a polyalkylene glycol mono(meth)acrylic acid ester monomer in which the average repeat number of alkylene oxide constituting the polyalkylene glycol chain is 3 to 14 and the diester content in the monomer is 0.2% or less. The acrylic polymer preferably does not contain any copolymerizable monomers containing a carboxyl group and no nitrogen-containing vinyl monomers that do not contain a hydroxyl group. Furthermore, a pressure-sensitive adhesive layer made of a pressure-sensitive adhesive composition containing, in addition to the acrylic polymer, (C) a difunctional or higher isocyanate compound, (D) a crosslinking accelerator, and (E) a keto-enol tautomer compound is preferred.

[0034] Among (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18, (a1) at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4 includes butyl (meth)acrylate, isobutyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and isopropyl (meth)acrylate. In addition, (a2) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of 5 to 18 include pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, and ethylhexyl (meth)acrylate. Examples of such acrylates include silyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, myristyl (meth)acrylate, isomyristyl (meth)acrylate, cetyl (meth)acrylate, isocetyl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate. It is preferable that the composition contains 1 to 30 parts by weight of (a1) at least one kind of (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C4 and 70 to 99 parts by weight of (a2) at least one kind of (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18, relative to a total of 100 parts by weight of (A) (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18, it is more preferable that the composition contains 5 to 25 parts by weight of at least one kind of (a1) and 75 to 95 parts by weight of at least one kind of (a2), and it is particularly preferable that the composition contains 8 to 22 parts by weight of at least one kind of (a1) and 78 to 92 parts by weight of at least one kind of (a2).

[0035] (B) Examples of copolymerizable monomers containing a hydroxyl group include hydroxyalkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate, as well as hydroxyl group-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. It is preferable that the monomer is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. These (B) copolymerizable monomers containing a hydroxyl group are different from the (F) polyalkylene glycol mono (meth)acrylic acid ester monomers described later and do not have a polyalkylene glycol chain. (B) at least one kind of copolymerizable monomer containing a hydroxyl group is copolymerized in an amount of preferably 0.1 to 12 parts by weight, more preferably 0.1 to 9.5 parts by weight, and particularly preferably 0.3 to 8 parts by weight, per 100 parts by weight of (A) (meth)acrylic acid ester monomers in total having an alkyl group carbon number of C1 to C18. In addition, when the total amount of the acrylic polymers is 100 parts by weight, the (B) hydroxyl group-containing copolymerizable monomer is preferably contained in an amount of 0.1 to 10 parts by weight, more preferably 0.1 to 8.5 parts by weight, and particularly preferably 0.3 to 7.5 parts by weight.

[0036] (C) The difunctional or higher isocyanate compound may be at least one or more selected from polyisocyanate compounds having at least two isocyanate (NCO) groups in one molecule. Polyisocyanate compounds are classified into aliphatic isocyanates, aromatic isocyanates, acyclic isocyanates, alicyclic isocyanates, etc., and any of them may be used. Specific examples of polyisocyanate compounds include aliphatic isocyanate compounds such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and trimethylhexamethylene diisocyanate (TMDI), and aromatic isocyanate compounds such as diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), hydrogenated xylylene diisocyanate (H6XDI), dimethyldiphenylene diisocyanate (TOID), and tolylene diisocyanate (TDI). Examples of trifunctional or higher isocyanate compounds include biuret modified or isocyanurate modified difunctional isocyanate compounds (compounds having two NCO groups in one molecule), and adducts (polyol modified compounds) with trivalent or higher polyols (compounds having at least three OH groups in one molecule) such as trimethylolpropane (TMP) or glycerin. As the difunctional or higher isocyanate compound (C), it is possible to use only the trifunctional isocyanate compound (C-1) or only the difunctional isocyanate compound (C-2). It is also possible to use the trifunctional isocyanate compound (C-1) and the difunctional isocyanate compound (C-2) in combination.

[0037] Furthermore, the (C-1) trifunctional isocyanate compound used in the present invention is selected from the (C-1-1) first aliphatic isocyanate compound group consisting of an isocyanurate of a hexamethylene diisocyanate compound, an isocyanurate of an isophorone diisocyanate compound, an adduct of a hexamethylene diisocyanate compound, an adduct of an isophorone diisocyanate compound, a biuret of a hexamethylene diisocyanate compound, and a biuret of an isophorone diisocyanate compound. In addition, it is preferable to include at least one or more selected from (C-1-2) a second aromatic isocyanate compound group consisting of an isocyanurate of a tolylene diisocyanate compound, an isocyanurate of a xylylene diisocyanate compound, an isocyanurate of a hydrogenated xylylene diisocyanate compound, an adduct of a tolylene diisocyanate compound, an adduct of a xylylene diisocyanate compound, and an adduct of a hydrogenated xylylene diisocyanate compound. It is preferable to use (C-1-1) the first aliphatic isocyanate compound group and (C-1-2) the second aromatic isocyanate compound group in combination. In the present invention, the balance of adhesive strength between the low-speed peeling region and the high-speed peeling region can be further improved by using, as the (C-1) trifunctional isocyanate compound, at least one selected from the (C-1-1) first group of aliphatic isocyanate compounds and at least one selected from the (C-1-2) second group of aromatic isocyanate compounds in combination.

[0038] In addition, the (C-1) trifunctional isocyanate compound contains at least one selected from the (C-1-1) first aliphatic isocyanate compound group and at least one selected from the (C-1-2) second aromatic isocyanate compound group, and is preferably contained in a total amount of 0.5 to 5.0 parts by weight per 100 parts by weight of the acrylic polymer. In addition, the mixing ratio of at least one selected from the (C-1-1) first aliphatic isocyanate compound group and at least one selected from the (C-1-2) second aromatic isocyanate compound group is preferably within the range of 10%:90% to 90%:10% by weight (C-1-1):(C-1-2).

[0039] Furthermore, the (C-2) bifunctional isocyanate compound used in the present invention is preferably an acyclic aliphatic isocyanate compound, which is a compound produced by reacting a diisocyanate compound with a diol compound. For example, when a diisocyanate compound is represented by the general formula "O=C=NXN=C=O" (where X is a divalent group) and a diol compound is represented by the general formula "HO-Y-OH" (where Y is a divalent group), an example of a compound produced by reacting a diisocyanate compound with a diol compound is a compound represented by the following general formula Z.

[0040] [General formula Z] O=C=NX-(NH-CO-OYO-CO-NH-X) n -N=C=O

[0041] Here, n is an integer of 0 or more. When n is 0, the general formula Z represents "O=C=NXN=C=O". The bifunctional acyclic aliphatic isocyanate compound may contain a compound in which n is 0 in the general formula Z (a diisocyanate compound unreacted with a diol compound), but it is preferable to contain a compound in which n is an integer of 1 or more as an essential component. The bifunctional acyclic aliphatic isocyanate compound may be a mixture of multiple compounds in which n in the general formula Z is different.

[0042] The diisocyanate compound represented by the general formula "O=C=NXN=C=O" is an aliphatic diisocyanate. X is preferably an acyclic aliphatic divalent group. The aliphatic diisocyanate is preferably one or more selected from the group consisting of tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate.

[0043] The diol compound represented by the general formula "HO-Y-OH" is an aliphatic diol. Y is preferably an acyclic aliphatic divalent group. The diol compound is preferably one or more selected from the group consisting of 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol monohydroxypivalate, polyethylene glycol, and polypropylene glycol.

[0044] The weight ratio (C-1 / C-2) of the (C-1) trifunctional isocyanate compound to the (C-2) difunctional isocyanate compound is preferably 1 to 90. The (C) di- or higher functional isocyanate compound is preferably 0.1 to 10 parts by weight based on 100 parts by weight of the acrylic polymer.

[0045] The (D) crosslinking accelerator may be any substance that functions as a catalyst for the reaction (crosslinking reaction) between the acrylic polymer and the crosslinking agent when a polyisocyanate compound is used as the crosslinking agent, and examples of such crosslinking accelerator include amine compounds such as tertiary amines, metal chelate compounds, organotin compounds, organolead compounds, organozinc compounds, and other organometallic compounds. In the present invention, the crosslinking accelerator is preferably a metal chelate compound or an organotin compound.

[0046] A metal chelate compound is a compound in which one or more polydentate ligands L are bonded to a central metal atom M. The metal chelate compound may or may not have one or more monodentate ligands X bonded to the metal atom M. For example, the general formula of a metal chelate compound having one metal atom M is M(L) m (X) n When m is 2 or more, m L's may be the same ligand or different ligands. When n is 2 or more, n X's may be the same ligand or different ligands.

[0047] Examples of the metal atom M include Fe, Ni, Mn, Cr, V, Ti, Ru, Zn, Al, Zr, and Sn. Examples of the polydentate ligand L include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone (also known as 2,4-pentanedione), 2,4-hexanedione, and benzoylacetone. These are keto-enol tautomer compounds, and in the polydentate ligand L, the enol may be deprotonated to form an enolate (e.g., acetylacetonate). Examples of the monodentate ligand X include halogen atoms such as chlorine and bromine atoms, acyloxy groups such as pentanoyl, hexanoyl, 2-ethylhexanoyl, octanoyl, nonanoyl, decanoyl, dodecanoyl, and octadecanoyl groups, and alkoxy groups such as methoxy, ethoxy, n-propoxy, isopropoxy, and butoxy groups.

[0048] Specific examples of metal chelate compounds include iron tris(2,4-pentanedionato)(III), iron trisacetylacetonate, titanium trisacetylacetonate, ruthenium trisacetylacetonate, zinc bisacetylacetonate, aluminum trisacetylacetonate, zirconium tetrakisacetylacetonate, iron tris(2,4-hexanedionato)(III), zinc bis(2,4-hexanedionato), titanium tris(2,4-hexanedionato), aluminum tris(2,4-hexanedionato), and zirconium tetrakis(2,4-hexanedionato).

[0049] Examples of organotin compounds include dialkyltin oxide, fatty acid salts of dialkyltin, and fatty acid salts of stannous tin. Traditionally, dibutyltin compounds have been widely used, but in recent years, the toxicity of organotin compounds has been pointed out, and tributyltin (TBT) contained in dibutyltin compounds in particular is also a concern as an endocrine disrupting substance. From the viewpoint of safety, long-chain alkyltin compounds such as dioctyltin compounds are preferred. Specific examples of organotin compounds include dioctyltin oxide and dioctyltin dilaurate. Although Sn compounds can be used provisionally, in the future, in view of the trend toward the use of safer substances, it is preferable to use metal chelate compounds such as Al, Ti, and Fe, which are safer than Sn. The crosslinking accelerator (D) in the pressure-sensitive adhesive composition according to the present invention is preferably at least one selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds. The crosslinking accelerator (D) is preferably contained in an amount of 0.001 to 0.5 parts by weight based on 100 parts by weight of the acrylic polymer.

[0050] Examples of the (E) keto-enol tautomer compound include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. In a pressure-sensitive adhesive composition using a polyisocyanate compound as a crosslinking agent, these compounds block the isocyanate groups of the crosslinking agent, thereby suppressing excessive viscosity increase and gelation of the pressure-sensitive adhesive composition after blending the crosslinking agent, and thereby extending the pot life of the pressure-sensitive adhesive composition. The (E) keto-enol tautomer compound is preferably contained in an amount of 0.1 to 300 parts by weight based on 100 parts by weight of the acrylic polymer.

[0051] Since the (E) keto-enol tautomer compound has an effect of suppressing crosslinking, in contrast to the (D) crosslinking accelerator, it is preferable to appropriately set the ratio of the (E) keto-enol tautomer compound to the (D) crosslinking accelerator. In order to extend the pot life of the pressure-sensitive adhesive composition and improve its storage stability, the weight ratio of (E) / (D) is preferably 70 to 1000, more preferably 70 to 700, and particularly preferably 80 to 600.

[0052] The acrylic polymer may further contain (F) a polyalkylene glycol mono(meth)acrylic acid ester monomer as an optional component of the copolymerizable monomer group. The (F) polyalkylene glycol mono(meth)acrylic acid ester monomer may be a compound in which one of the multiple hydroxyl groups of a polyalkylene glycol is esterified as a (meth)acrylic acid ester. The (meth)acrylic acid ester group is a polymerizable group, and therefore can be copolymerized with the acrylic polymer. The other hydroxyl groups may remain as OH or may be alkyl ethers such as methyl ether or ethyl ether, or saturated carboxylate esters such as acetate ester, or the like. The alkylene group of the polyalkylene glycol includes, but is not limited to, an ethylene group, a propylene group, a butylene group, etc. The polyalkylene glycol may be a copolymer of two or more polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polybutylene glycol, etc. The copolymer of polyalkylene glycol includes polyethylene glycol-polypropylene glycol, polyethylene glycol-polybutylene glycol, polypropylene glycol-polybutylene glycol, etc., and the copolymer may be a block copolymer or a random copolymer. It is preferable that the (F) polyalkylene glycol mono(meth)acrylate monomer has an average repeat number of alkylene oxide constituting the polyalkylene glycol chain of 3 to 14. The "average repeat number of alkylene oxide" refers to the average number of repeating alkylene oxide units in the "polyalkylene glycol chain" portion contained in the molecular structure of the (F) polyalkylene glycol mono(meth)acrylate monomer. In the (F) polyalkylene glycol mono(meth)acrylic acid ester monomer, the diester content in the monomer is preferably 0.2% or less. The "diester content in the monomer" refers to the content (wt%) of polyalkylene glycol di(meth)acrylic acid ester contained in the (F) polyalkylene glycol mono(meth)acrylic acid ester monomer.

[0053] The (F) polyalkylene glycol mono(meth)acrylic acid ester monomer is preferably at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate. More specifically, polyethylene glycol-mono(meth)acrylate, polypropylene glycol-mono(meth)acrylate, polybutylene glycol-mono(meth)acrylate, polyethylene glycol-polypropylene glycol-mono(meth)acrylate, polyethylene glycol-polybutylene glycol-mono(meth)acrylate, polypropylene glycol-polybutylene glycol-mono(meth)acrylate, polyethylene glycol-polypropylene glycol-polybutylene glycol-mono(meth)acrylate; methoxypolyethylene glycol-(meth)acrylate, methoxypolypropylene glycol-(meth)acrylate, methoxypolybutylene glycol-(meth)acrylate, methoxy-polyethylene glycol-polypropylene glycol-(meth)acrylate, methoxy-polyethylene glycol methoxy-polybutylene glycol-polybutylene glycol-(meth)acrylate, methoxy-polyethylene glycol-polypropylene glycol-polybutylene glycol-(meth)acrylate; ethoxypolyethylene glycol-(meth)acrylate, ethoxypolypropylene glycol-(meth)acrylate, ethoxypolybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polypropylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polypropylene glycol-polybutylene glycol-(meth)acrylate, ethoxy-polyethylene glycol-polypropylene glycol-polybutylene glycol-(meth)acrylate, and the like. When the total of (A) (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18 is 100 parts by weight, the (F) polyalkylene glycol mono(meth)acrylic acid ester monomer is preferably contained in an amount of 0 to 50 parts by weight. In the pressure-sensitive adhesive layer according to the present invention, the pressure-sensitive adhesive composition does not necessarily need to contain (F) polyalkylene glycol mono(meth)acrylic acid ester monomer.

[0054] The pressure-sensitive adhesive composition may optionally contain (H) a polyether-modified siloxane compound having an HLB value of 7 to 15. The polyether-modified siloxane compound is a siloxane compound having a polyether group, and has a general siloxane unit [-SiR 1 2-O-], as well as siloxane units with polyether groups [-SiR 1 (R 2 O(R 3 O) n R 4 )-O-], where R 1 is one or more alkyl or aryl groups, R 2 and R 3 is one or more alkylene groups, R 4 indicates one or more alkyl or acyl groups (terminal groups). The polyether group is a polyoxyethylene group [(C2H4O) n 〕 and polyoxypropylene group〔(C3H6O) n ] and the like polyoxyalkylene groups.

[0055] The polyether-modified siloxane compound is preferably a polyether-modified siloxane compound having an HLB value of 7 to 15. The polyether-modified siloxane compound having an HLB value of 7 to 15 is preferably contained in an amount of 1.0 part by weight or less (except for the case of 0 part by weight), 0.01 to 1.0 part by weight, and more preferably 0.1 to 0.5 parts by weight, per 100 parts by weight of the acrylic polymer. HLB is the hydrophilic-lipophilic balance (hydrophilic-lipophilic ratio) defined in, for example, JIS K3211 (terminology for surfactants).

[0056] Polyether-modified siloxane compounds can be obtained, for example, by grafting an organic compound having an unsaturated bond and a polyoxyalkylene group onto a polyorganosiloxane main chain having a silicon hydride group by a hydrosilylation reaction. Specific examples include dimethylsiloxane-methyl(polyoxyethylene)siloxane copolymer, dimethylsiloxane-methyl(polyoxyethylene)siloxane-methyl(polyoxypropylene)siloxane copolymer, and dimethylsiloxane-methyl(polyoxypropylene)siloxane polymer. The HLB value of the polyether-modified siloxane compound can be adjusted by selecting the ratio of the polyether group to the siloxane group. The adhesive strength and staining resistance of the adhesive can be improved by blending the adhesive composition with (H) a polyether-modified siloxane compound having an HLB value of 7 to 15. When the adhesive composition does not contain a polyether-modified siloxane compound, the cost becomes lower.

[0057] Furthermore, as other components, the pressure-sensitive adhesive composition of the present invention may appropriately contain known additives such as surfactants, curing accelerators, plasticizers, fillers, curing retarders, processing aids, antioxidants, antioxidants, etc. These may be used alone or in combination of two or more kinds.

[0058] The acrylic polymer used in the pressure-sensitive adhesive composition of the present invention can be synthesized by copolymerizing (a1) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C4 in an amount of 1 to 30 parts by weight, (a2) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18 in an amount of 70 to 99 parts by weight, and (B) at least one copolymerizable monomer containing a hydroxyl group in an amount of 0.1 to 12 parts by weight, based on a total of 100 parts by weight of (A) (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18. The copolymerizable monomer group may further include (F) a polyalkylene glycol mono(meth)acrylic acid ester monomer. The polymerization method of the acrylic polymer is not particularly limited, and any appropriate polymerization method such as solution polymerization or emulsion polymerization can be used. The pressure-sensitive adhesive composition of the present invention can be prepared by blending an acrylic polymer with (C) a difunctional or higher isocyanate compound, (D) a crosslinking accelerator, and (E) a keto-enol tautomer compound, and further with any additives as appropriate.

[0059] The acrylic polymer does not contain a copolymerizable monomer containing a carboxyl group or a nitrogen-containing vinyl monomer not containing a hydroxyl group as a copolymerizable monomer group, which is effective in improving the crosslinking rate and stabilizing the adhesive strength. It is preferable to use a copolymerizable monomer containing a hydroxyl group (B) as a monomer that reacts with a difunctional or higher isocyanate compound (C) used as a crosslinking agent. Preferred monomer compositions for the acrylic polymer include at least one type each of (A) and (B), at least one type each of (A), (B), and (F), etc.

[0060] The adhesive layer obtained by crosslinking the adhesive composition preferably has an adhesive strength of 0.05 to 0.1 N / 25 mm at a low peeling speed of 0.3 m / min, and an adhesive strength of 1.0 N / 25 mm or less at a high peeling speed of 30 m / min. This provides performance with little change in adhesive strength depending on the peeling speed, and enables rapid peeling even at high-speed peeling. In addition, when the antistatic surface protective film is peeled off once for re-adhesion, it does not require excessive force and is easy to peel off from the adherend.

[0061] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a surface resistivity of 5.0×10 +12 It is preferable that the surface resistivity is Ω / □ or less, and the peeling electrification voltage is "±0.6 kV or less". In the present invention, "±0.6 kV or less" means 0 to -0.6 kV and 0 to +0.6 kV, i.e., -0.6 to +0.6 kV. If the surface resistivity is high, the performance of dissipating static electricity generated by charging when the antistatic surface protection film is peeled off from the adherend is poor. Therefore, by making the surface resistivity sufficiently small, the peeling electrification voltage generated by static electricity generated when the pressure-sensitive adhesive layer is peeled off from the adherend is reduced, and it is possible to suppress the influence on the electric control circuit of the adherend.

[0062] The gel fraction of the pressure-sensitive adhesive layer (crosslinked pressure-sensitive adhesive) obtained by crosslinking the pressure-sensitive adhesive composition of the present invention is preferably 95 to 100%. With such a high gel fraction, the adhesive strength is not excessively high at a low peel speed, and the elution of unpolymerized monomers or oligomers from the acrylic polymer is reduced, improving the staining resistance and durability at high temperatures and high humidity, and making it possible to suppress staining of the adherend.

[0063] The antistatic surface protective film of the present invention is formed by forming an adhesive layer formed by crosslinking an adhesive composition on one or both sides of a resin film. The antistatic surface protective film of the present invention is formed by forming an adhesive layer formed by crosslinking an adhesive composition in which the above-mentioned components (A) to (E) are well-balanced, and therefore has excellent antistatic performance, an excellent balance of adhesive strength at low and high peeling speeds, and also excellent durability and anti-fouling properties. Therefore, it can be suitably used as a surface protective film for a polarizing plate.

[0064] The thickness of the adhesive layer 2 used in the antistatic surface protective film 10 according to the present invention is not particularly limited, but is preferably about 5 to 40 μm, and more preferably about 10 to 30 μm. The adhesive layer 2 preferably has a weak adhesive strength, that is, a peel strength (adhesive strength) of the antistatic surface protective film to the surface of the adherend of about 0.03 to 0.3 N / 25 mm, because this provides excellent operability when peeling the antistatic surface protective film from the adherend. In addition, the peel strength of the release film 5 from the adhesive layer 2 is preferably 0.2 N / 50 mm or less, because this provides excellent operability when peeling the release film 5 from the antistatic surface protective film 10.

[0065] Furthermore, the release film 5 used in the antistatic surface protective film 10 according to the present invention has a release agent layer 4 formed on one side of a resin film 3, the release agent layer 4 being made of a resin composition containing a release agent mainly composed of dimethylpolysiloxane and an antistatic agent. The release agent layer 4 preferably further contains a silicone-based compound that is liquid at 20° C. The silicone-based compound in the release agent layer 4 is preferably a polyether-modified silicone.

[0066] Examples of the resin film 3 include polyester film, polyamide film, polyethylene film, polypropylene film, and polyimide film, among which polyester film is particularly preferred due to its excellent transparency and relatively low price. The resin film may be a non-stretched film or a uniaxially or biaxially stretched film. In addition, the stretching ratio of the stretched film and the axial orientation angle formed by the crystallization of the stretched film may be controlled to a specific value. The thickness of the resin film 3 is not particularly limited, but is preferably, for example, about 12 to 100 μm, and more preferably about 20 to 50 μm for ease of handling. If necessary, the surface of the resin film 3 may be subjected to a treatment for improving adhesion, such as surface modification by corona discharge or application of an anchor coating agent.

[0067] The release agent mainly composed of dimethylpolysiloxane constituting the release agent layer 4 includes known silicone-based release agents such as addition reaction type, condensation reaction type, cationic polymerization type, and radical polymerization type. Examples of products commercially available as addition reaction type silicone-based release agents include KS-776A, KS-847T, KS-779H, KS-837, KS-778, and KS-830 (manufactured by Shin-Etsu Chemical Co., Ltd.), SRX-211, SRX-345, SRX-357, SD7333, SD7220, SD7223, LTC-300B, LTC-350G, and LTC-310 (manufactured by Dow Corning Toray Co., Ltd.). Examples of products commercially available as condensation reaction type release agents include SRX-290 and SYLOFF-23 (manufactured by Dow Corning Toray Co., Ltd.). Examples of commercially available cationic polymerization products include TPR-6501, TPR-6500, UV9300, VU9315, UV9430 (manufactured by Momentive Performance Materials, Inc.), and X62-7622 (manufactured by Shin-Etsu Chemical Co., Ltd.). Examples of commercially available radical polymerization products include X62-7205 (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0068] Examples of silicone compounds that are liquid at 20°C and that constitute the release agent layer 4 include polyether-modified silicone, alkyl-modified silicone, and carbinol higher fatty acid ester-modified silicone. In the present invention, in order to improve the antistatic properties of the surface of the pressure-sensitive adhesive layer, a silicone compound that is liquid at 20°C and is compatible with the release agent layer mainly composed of dimethylpolysiloxane is used. For the purposes of the present invention, polyether-modified silicone is preferred among modified silicone compounds. The polyether chain in the polyether-modified silicone is composed of ethylene oxide, propylene oxide, etc., and for example, the physical properties such as compatibility with the silicone release agent and antistatic effect can be adjusted by selecting the molecular weight of the polyethylene oxide used in the side chain. In addition, examples of commercially available polyether-modified silicone products include KF-351A, KF-352A, KF-353, KF-354L, KF-355A, and KF-642 (manufactured by Shin-Etsu Chemical Co., Ltd.), SH8400, SH8700, and SF8410 (manufactured by Dow Corning Toray Co., Ltd.), TSF-4440, TSF-4441, TSF-4445, TSF-4446, and TSF-4450 (manufactured by Momentive Performance Materials), BYK-300, BYK-306, BYK-307, BYK-320, BYK-325, and BYK-330 (manufactured by BYK-Chemie). The amount of silicone-based compound that is liquid at 20°C to be added to a release agent containing dimethylpolysiloxane as its main component varies depending on the type of silicone-based compound and the degree of compatibility with the release agent, but can be set taking into consideration the desired peeling electrification voltage, contamination of the adherend, adhesive properties, etc. when the antistatic surface protection film is peeled off from the adherend.

[0069] The antistatic agent constituting the release agent layer 4 is preferably one that has good dispersibility in the release agent solution mainly composed of dimethylpolysiloxane and does not inhibit the hardening of the release agent mainly composed of dimethylpolysiloxane. An alkali metal salt is suitable as such an antistatic agent.

[0070] Examples of the alkali metal salt include metal salts of lithium, sodium, and potassium. + , Na + , K + and a cation consisting of Cl - , Br - , I - , BF4 - , PF6 - , SCN - , ClO4 - , CF3SO3 - , (FSO2)2N - , (CF3SO2)2N - , (C2F5SO2)2N - , (CF3SO2)3C - Metal salts composed of anions consisting of the above are preferably used. Among them, lithium salts (Li salts) such as LiBr, LiI, LiBF4, LiPF6, LiSCN, LiClO4, LiCF3SO3, Li(FSO2)2N, Li(CF3SO2)2N, Li(C2F5SO2)2N, and Li(CF3SO2)3C are particularly preferably used, and Li(CF3SO2)2N (abbreviated as LiTFSI), Li(FSO2)2N (abbreviated as LiFSI), and LiCF3SO3 (abbreviated as LiTF or LiTf). These alkali metal salts may be used alone or in combination of two or more. In order to stabilize the ionic substance, a compound containing a polyoxyalkylene structure may be added. The amount of antistatic agent added to a release agent containing dimethylpolysiloxane as a main component varies depending on the type of antistatic agent and the degree of affinity with the release agent, but can be set taking into consideration the desired peeling electrification voltage, contamination of the adherend, adhesion characteristics, etc. when the antistatic surface protection film is peeled off from the adherend.

[0071] There is no particular limitation on the method of mixing the release agent mainly composed of dimethylpolysiloxane with the antistatic agent. Any method may be used, such as a method of adding an antistatic agent to a release agent mainly composed of dimethylpolysiloxane, mixing, and then adding and mixing a catalyst for hardening the release agent, a method of diluting a release agent mainly composed of dimethylpolysiloxane with an organic solvent in advance, and then adding and mixing an antistatic agent and a catalyst for hardening the release agent, or a method of diluting a release agent mainly composed of siloxane with an organic solvent in advance, adding and mixing a catalyst, and then adding and mixing an antistatic agent. In addition, if necessary, a material that assists the antistatic effect, such as an adhesion improver such as a silane coupling agent or a compound containing a polyoxyalkylene group, may be added. The method for mixing the polyether-modified silicone with the release agent is the same as the method for mixing the antistatic agent, and there are no particular limitations.

[0072] The mixing ratio of the release agent mainly composed of dimethylpolysiloxane and the antistatic agent is not particularly limited, but the ratio of the antistatic agent as a solid content is preferably about 5 to 100 to 100 to 100 of the solid content of the release agent mainly composed of dimethylpolysiloxane. If the amount of the antistatic agent added in terms of solid content is less than 5 to 100 of the solid content of the release agent mainly composed of dimethylpolysiloxane, the amount of the antistatic agent transferred to the surface of the adhesive layer is also reduced, making it difficult for the adhesive to exhibit its antistatic function. In addition, if the amount of the antistatic agent added in terms of solid content exceeds 100 to 100 of the solid content of the release agent mainly composed of dimethylpolysiloxane, the release agent mainly composed of dimethylpolysiloxane is also transferred to the surface of the adhesive layer together with the antistatic agent, which may reduce the adhesive properties of the adhesive. The mixing ratio of the polyether-modified silicone to the release agent is preferably approximately the same as the mixing ratio of the antistatic agent, but is not particularly limited.

[0073] The method for forming the adhesive layer 2 on the base film 1 of the antistatic surface protective film 10 according to the present invention and the method for laminating the release film 5 may be performed by known methods and are not particularly limited. Specifically, examples of the method include (1) a method in which an adhesive composition for forming the adhesive layer 2 is applied to one side of the base film 1, dried to form an adhesive layer, and then laminating the release film 5, and (2) a method in which an adhesive composition for forming the adhesive layer 2 is applied to the surface of the release film 5, dried to form an adhesive layer, and then laminating the base film 1, and any of these methods may be used.

[0074] The pressure-sensitive adhesive layer 2 may be formed on the surface of the base film 1 by a known method. Specifically, known coating methods such as reverse coating, comma coating, gravure coating, slot die coating, Mayer bar coating, and air knife coating can be used.

[0075] Similarly, the release agent layer 4 may be formed on the resin film 3 by a known method. Specifically, known coating methods such as gravure coating, Mayer bar coating, and air knife coating can be used.

[0076] FIG. 2 is a cross-sectional view showing a state in which the release film has been peeled off from the antistatic surface protective film of the present invention. By peeling off the release film 5 from the antistatic surface protective film 10 shown in Fig. 1, a part of the antistatic agent (reference symbol 7) contained in the release agent layer 4 of the release film 5 is transferred (adhered) to the surface of the pressure-sensitive adhesive layer 2 of the antistatic surface protective film 10. Therefore, in Fig. 2, the antistatic agent transferred to the surface of the pressure-sensitive adhesive layer 2 of the antistatic surface protective film is diagrammatically shown by spots reference symbol 7. In the antistatic surface protective film according to the present invention, when the antistatic surface protective film 11 from which the release film shown in Fig. 2 has been peeled off is attached to an adherend, the antistatic agent transferred to the surface of the pressure-sensitive adhesive layer 2 comes into contact with the surface of the adherend, thereby making it possible to keep the peeling electrification voltage low when the antistatic surface protective film is peeled off from the adherend again.

[0077] FIG. 3 is a cross-sectional view showing an embodiment of an optical component according to the present invention. The release film 5 is peeled off from the antistatic surface protective film 10 of the present invention, and in a state where the pressure-sensitive adhesive layer 2 is exposed, the film is attached to an optical component 8 as an adherend via the pressure-sensitive adhesive layer 2 . That is, FIG. 3 shows an optical component 20 to which the antistatic surface protective film 10 of the present invention is attached. Examples of optical components include optical films such as a polarizing plate, a retardation plate, a lens film, a polarizing plate that also serves as a retardation plate, and a polarizing plate that also serves as a lens film. Such optical components are used as components of various display devices such as liquid crystal display panels and organic EL display panels, and optical devices of various instruments. Examples of optical components include optical films such as antireflection films, hard coat films, and transparent conductive films for touch panels. In particular, the antistatic surface protective film can be suitably used as an antistatic surface protective film attached to the antifouling surface of optical films such as low reflection polarizing plates (LR polarizing plates) and antiglare low reflection polarizing plates (AG-LR polarizing plates) whose surfaces are antifouling treated with silicone compounds, fluorine compounds, etc. Examples of the low-reflection surface treatment layer of the LR polarizing plate include metal oxide thin films (such as vapor deposition films of SiO2, TiO2, etc.), antireflection films of fluororesins, etc. The antistatic surface protective film of the present invention can achieve both reduced peeling electrification voltage and low contamination of the adherend, even when the pressure-sensitive adhesive layer of the antistatic surface protective film is attached in contact with these antireflection films. According to the optical component of the present invention, when the antistatic surface protective film 10 is peeled off and removed from the adherend, that is, the optical component (optical film), the peeling electrification voltage can be suppressed to a sufficiently low level, so that there is no risk of damaging circuit components such as driver ICs, TFT elements, and gate line driving circuits, and it is possible to improve production efficiency in the process of manufacturing liquid crystal display panels, organic EL display panels, etc., and maintain the reliability of the production process. EXAMPLES

[0078] The present invention will now be further described with reference to examples.

[0079] <Production of Pressure-Sensitive Adhesive Composition> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 10 parts by weight of methyl acrylate, 90 parts by weight of 2-ethylhexyl acrylate, 5.0 parts by weight of 8-hydroxyoctyl acrylate, 10 parts by weight of polypropylene glycol monoacrylate (n=12), and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution of Example 1 having a weight average molecular weight of 500,000. After adding 8.5 parts by weight of acetylacetone to this acrylic polymer solution and stirring, 2.0 parts by weight of coronate HX (isocyanurate of hexamethylene diisocyanate compound) and 0.1 parts by weight of titanium trisacetylacetonate were added and mixed with stirring to obtain a pressure-sensitive adhesive composition of Example 1.

[0080] [Examples 2 to 6 and Comparative Examples 1 to 3] Pressure-sensitive adhesive compositions of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the compositions of the pressure-sensitive adhesive composition of Example 1 were as shown in Tables 1 and 2. In Tables 1 and 2, the monomers contained (copolymerized) in the acrylic polymer are (A), (B), (F), and a "carboxyl group-containing monomer."

[0081] [Table 1]

[0082] [Table 2]

[0083] Tables 1 and 2 are two separate tables showing the blending ratios of each component, and in each case, the numerical values ​​in weight parts calculated with the total of group (A) being 100 parts by weight are shown in parentheses. Tables 3 and 4 show the compound names of the abbreviations of each component used in Tables 1 and 2. Note that Coronate (registered trademark) HX, Coronate (registered trademark) HL, and Coronate (registered trademark) L are product names of Tosoh Corporation, and Takenate (registered trademark) D-140N, D-127N, and D-110N are product names of Mitsui Chemicals, Inc. In "antistatic agent" in Table 2 and Table 7 described later, LiTFSI represents Li(CF3SO2)2N, LiFSI represents Li(FSO2)2N, and LiTF represents LiCF3SO3. In addition, in the compound used for the polyalkylene glycol mono(meth)acrylic acid ester monomer (F) in each example, the diester content in the monomer is 0.2% or less.

[0084] [Table 3]

[0085] [Table 4]

[0086] <Synthesis of bifunctional isocyanate compounds> The bifunctional isocyanate compounds of Synthesis Examples 1 and 2 were synthesized by the following method. As shown in Tables 5 and 6, a diisocyanate and a diol compound were mixed in a molar ratio of NCO / OH=16 and reacted at 120°C for 3 hours, and then the unreacted diisocyanate was removed under reduced pressure using a thin-film evaporator to obtain the desired bifunctional isocyanate compound.

[0087] [Table 5]

[0088] [Table 6]

[0089] <Preparation of antistatic surface protection film> [Example 1] 5 parts by weight of addition reaction type silicone (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-345), 0.15 parts by weight of polyether modified silicone (manufactured by Dow Corning Toray Co., Ltd., product name: SH8400, main component: dimethyl, methyl (polyethylene oxide acetate) siloxane), 0.5 parts by weight of Li(CF3SO2)2N, 95 parts by weight of a 1:1 mixed solvent of toluene and ethyl acetate, and 0.05 parts by weight of platinum catalyst (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-212 catalyst) were mixed and stirred to prepare a coating material for forming the release agent layer of Example 1. The coating material for forming the release agent layer of Example 1 was applied to the surface of a polyethylene terephthalate film having a thickness of 38 μm with a Mayer bar so that the thickness after drying was 0.2 μm, and the coating material was dried in a hot air circulating oven at 120° C. for 1 minute to obtain a release film of Example 1. The adhesive composition of Example 1 was applied to the surface of a polyethylene terephthalate film having a thickness of 38 μm so that the thickness after drying was 20 μm, and then dried for 2 minutes in a hot air circulating oven at 100° C. to form an adhesive layer. The release agent layer (silicone-treated surface) of the release film of Example 1 prepared above was then attached to the surface of this adhesive layer. The obtained adhesive film was kept warm in an environment of 40° C. for 5 days to cure the adhesive, and an antistatic surface protection film of Example 1 was obtained.

[0090] [Example 2] The antistatic surface protection film of Example 2 was obtained in the same manner as Example 1, except that the adhesive composition of Example 1 was replaced with the adhesive composition of Example 2 and the antistatic agent used in the release agent layer was replaced with LiCF3SO3.

[0091] [Examples 3 to 6] The antistatic surface protection films of Examples 3 to 6 were obtained in the same manner as in Example 1, except that the adhesive composition of Example 1 was replaced with the adhesive compositions of Examples 3 to 6, and the antistatic agent used in the release agent layer was changed to Li(FSO2)2N.

[0092] [Comparative Example 1] 5 parts by weight of addition reaction type silicone (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-345), 95 parts by weight of a 1:1 mixed solvent of toluene and ethyl acetate, and 0.05 parts by weight of a platinum catalyst (manufactured by Dow Corning Toray Co., Ltd., product name: SRX-212 catalyst) were mixed and stirred to prepare a coating material for forming the release agent layer of Comparative Example 1. The coating material for forming the release agent layer of Comparative Example 1 was applied to the surface of a polyethylene terephthalate film having a thickness of 38 μm with a Mayer bar so that the thickness after drying would be 0.2 μm, and the coating material was dried in a hot air circulating oven at 120° C. for 1 minute to obtain a release film of Comparative Example 1. The adhesive composition of Comparative Example 1 was applied to the surface of a polyethylene terephthalate film having a thickness of 38 μm so that the thickness after drying was 20 μm, and then dried for 2 minutes in a hot air circulating oven at 100° C. to form an adhesive layer. Then, the release agent layer (silicone-treated surface) of the release film of Comparative Example 1 prepared above was attached to the surface of this adhesive layer. The obtained adhesive film was kept warm in an environment of 40° C. for 5 days to cure the adhesive, and an antistatic surface protection film of Comparative Example 1 was obtained.

[0093] [Comparative Example 2] An antistatic surface protection film of Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the adhesive composition of Comparative Example 1 was replaced with the adhesive composition of Comparative Example 2.

[0094] [Comparative Example 3] An antistatic surface protection film of Comparative Example 3 was obtained in the same manner as in Example 1, except that the adhesive composition of Example 1 was replaced with the adhesive composition of Comparative Example 3 and the antistatic agent used in the release agent layer was replaced with Li(FSO2)2N.

[0095] Table 7 shows the compositions of the release agent layers in the antistatic surface protection films of Examples 1-6 and Comparative Examples 1-3.

[0096] [Table 7]

[0097] <Test methods and evaluation> The antistatic surface protection films of Examples 1 to 6 and Comparative Examples 1 to 3 were aged for 7 days under an atmosphere of 23°C and 50% RH, and then the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, which was used as a sample for measuring surface resistivity. Furthermore, this antistatic surface protection film with the adhesive layer exposed was attached to the surface of a polarizing plate attached to a liquid crystal cell via the adhesive layer, and after leaving it for one day, it was autoclaved at 50°C and 5 atmospheres for 20 minutes and then left at room temperature for a further 12 hours to prepare a sample for measuring adhesive strength, peeling charge voltage, and contamination properties.

[0098] <Adhesive strength> The measurement sample obtained above (a 25 mm wide antistatic surface protection film bonded to the surface of a polarizing plate) was peeled in a 180° direction at a low peeling speed (0.3 m / min) and a high peeling speed (30 m / min) using a tensile tester, and the measured peel strength was taken as the adhesive strength.

[0099] <Surface resistivity> After aging and before bonding to a polarizing plate, the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, and the surface resistivity of the adhesive layer was measured using a resistivity meter, Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).

[0100] <Peeling charge voltage> The measurement sample obtained above was peeled off at an angle of 180° at a tensile speed of 30 m / min, and the voltage (charged voltage) generated by the polarizing plate being charged was measured using high-precision electrostatic sensors SK-035 and SK-200 (manufactured by Keyence Corporation). The maximum measured value was taken as the peeling charged voltage.

[0101] <Staining> A polarizing plate that has been subjected to low reflection surface treatment is attached to one side of a glass plate via an adhesive layer (e.g., a double-sided adhesive tape different from the adhesive layer of the antistatic surface protective film) using a laminating machine. Then, an antistatic surface protective film is attached to the surface of the polarizing plate using a laminating machine. After storing the polarizing plate in an environment of 23°C and 50% RH for periods of 3 days and 30 days, the antistatic surface protective film is peeled off and the contamination state of the polarizing plate surface is visually observed. Regarding surface contamination, a case in which there was no contamination on the surface of the polarizing plate after either 3-day storage or 30-day storage was rated as "○", a case in which there was slight contamination after either 3-day storage or 30-day storage was rated as "△", and a case in which there was contamination was rated as "×".

[0102] The evaluation results are shown in Table 8. The surface resistivity is expressed as "m×10 +n " is expressed as "mE+n" (where m is any real value and n is a positive integer).

[0103] [Table 8]

[0104] The measurement results shown in Table 8 reveal the following: The antistatic surface protection films of Examples 1 to 6 according to the present invention have appropriate adhesive strength, do not stain the surface of the adherend, and have a low peel electrification voltage when peeled off from the adherend. On the other hand, the antistatic surface protection film of Comparative Example 1 in which an antistatic agent was added to the adhesive layer had a low and favorable surface resistivity of the adhesive layer, but was somewhat inferior in terms of stain resistance. In addition, the antistatic surface protection film of Comparative Example 2 had high adhesive strength, high peeling electrification voltage, and slightly poor contamination resistance, possibly due to the addition of an antistatic agent to the adhesive layer as well as large amounts of (a1) (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4 and (B) copolymerizable monomer containing a hydroxyl group. In addition, the antistatic surface protection film of Comparative Example 3 had high adhesive strength and poor stain resistance because the acrylic polymer did not contain (a1) a (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4, but contained a monomer containing a carboxyl group. That is, in Comparative Examples 1 and 2 in which an antistatic agent was mixed into the pressure-sensitive adhesive layer, it was difficult to achieve both a reduction in peeling electrification voltage and low staining of the adherend. On the other hand, in Examples 1 to 6 in which an antistatic agent was added to the release agent layer and then the antistatic agent contained in the release agent layer was transferred to the surface of the pressure-sensitive adhesive layer, even adding a small amount of antistatic agent to the release agent layer had the effect of reducing peeling electrification voltage, so that there was no staining of the adherend and a good antistatic surface protection film was obtained. [Industrial Applicability]

[0105] The antistatic surface protective film of the present invention can be used, for example, in the production process of optical films such as polarizing plates, retardation plates, and lens films for displays, as well as various other optical components, to protect the surfaces of the optical components, etc. In particular, when used as an antistatic surface protective film for optical films such as LR polarizing plates and AG-LR polarizing plates, the surface of which has been anti-soiling treated with a silicone compound, a fluorine compound, etc., the amount of static electricity generated when peeled off from an adherend can be reduced. The antistatic surface protective film of the present invention causes little contamination of the substrate and has excellent antistatic performance upon peeling without deterioration over time, and therefore can improve the yield in the production process of optical films, optical components, etc., and is of great industrial value. [Explanation of symbols]

[0106] Reference Signs List 1...base film, 2...adhesive layer, 3...resin film, 4...release agent layer, 5...release film, 7...antistatic agent, 8...adherend (optical component), 10...antistatic surface protective film, 11...antistatic surface protective film with the release film removed, 20...optical component with antistatic surface protective film bonded thereto.

Claims

[Claim 1] An antistatic surface protection film comprising a substrate made of a transparent resin and a pressure-sensitive adhesive layer formed by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent, and a release film having a resin film and a release agent layer containing an antistatic agent laminated on one side of the resin film and laminated to the surface of the pressure-sensitive adhesive layer via the release agent layer, The acrylic polymer is (A) 100 parts by weight of a total of (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18; (B) 0.1 to 12 parts by weight of at least one copolymerizable monomer containing a hydroxyl group; (F) an acrylic polymer obtained by copolymerizing 5 to 50 parts by weight of a polyalkylene glycol mono(meth)acrylic acid ester monomer; Of 100 parts by weight of the (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18, (a1) 10 to 30 parts by weight of at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4; (a2) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18 is contained in an amount of 70 to 90 parts by weight, The acrylic polymer is not copolymerized with a copolymerizable monomer containing a carboxyl group and a nitrogen-containing vinyl monomer not containing a hydroxyl group, (a1) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4, and at least one selected from the group consisting of methyl (meth)acrylate and ethyl (meth)acrylate, in an amount of 10 to 20 parts by weight; The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has an adhesive strength of 0.05 to 0.1 N / 25 mm at a low peel speed of 0.3 m / min, and an adhesive strength of 1.0 N / 25 mm or less at a high peel speed of 30 m / min.

Citation Information

Patent Citations

  • Antistatic surface protective film

    JP2015131414A

  • Antistatic surface protective film

    JP2015217557A

  • Manufacturing method of antistatic surface protective film, and antistatic surface protective film

    JP2017156445A

  • Surface protecting film and optical component whereon it is stuck

    JP2005131957A

  • Adhesive composition, adhesive sheet and surface-protective film

    JP2005314476A